La facturación electrónica como herramienta para la reducción de sanciones vinculadas a declaraciones presentadas a la administración tributaria - Hurtado Ramirez, Carlos Dario (2015)
The main objective is to foster technological innovation, demonstrating that generates economic benefits in addition to greatly improve the opportunities for companies in response to the problems in the globalized world of today for the decision-making. The laws in the Ecuador support the proposal developed in base of mandatory requirements for the majority of the legal entities in accordance with the ideals of government, which has improved transcendentally management in the collection of taxes through stricter policies and punishments more quantitative. In addition, it complements this with information of scientific articles related to business issues, and is all of the documents (financial statements, vouchers and others requested by the regulatory bodies). As a result of the intervention were found substantial values disbursed to the state treasury at the rate of penalties and interest, which are not part of the budget for any company and directly attack with legal continuity and correct progress of activities. The posthumous development of the project it is concluded that the economic possibilities are no obstacle to the implementation benefits to the economy of both the company and the country, by means of statements undamaged that inject the required available to the general budget of the state for the continued development of works in the national territory, investments in strategic sectors related to the change of the productive matrix and other topics related to public spending. The final recommendation of this research is to be versatile before the changes, although it is true that the taxpayers have been kept in a so-called sedentary during tax years, the reality of the country is another today and it is always a good idea to keep abreast of the provisions that inform agencies of control.